The Effect of Steel Plate Thickness on the Behavior of Composite Shear Wall - عيسى نعمان (Latakia University Journal -Engineering Sciences Series, 2020)
Here we present an analytical study of a composite shear wall (CSW) containing a concrete wall on one side of the steel plate. As is known, the steel shear walls work to resist the lateral forces through the formation of tensile fields and buckling in steel plate. As for composite steel shear walls, It is different because of the presence of the concrete wall that works to prevent the buckling in the steel plate and here the steel plate works to resist the forces by shear only. The thickness of the steel plate plays an important role and directly affecting the shear resistance and the maximum resistance of the composite steel wall, in addition to the possibility of reducing the local buckling of the steel plate that is formed in the free distance for the shear stud spacing that supply a combination work of the plate and the concrete wall when the concrete wall is exists from one side. This is in addition to improving the plasticity and dissipative energy of the wall, and this was observed through the analytical study of four composite shear walls of similar size with each other in terms of engineering and structural composition, but they differ in the thickness of the steel plate, where we observed an increase in resistance by 18% when increasing the thickness by 50%.